WF10 stimulates NK cell cytotoxicity by increasing LFA-1-mediated adhesion to tumor cells - Kühne, Louisa; Konstandin, Mathias; Samstag, Yvonne; Meuer, Stefan; Giese, Thomas; Watzl, Carsten (Journal of biomedicine and biotechnology, 2011)
The redox-active chlorite-based drug WF10 (Immunokine) was shown to have modulatory effects on both the innate and adaptive immune system in vitro and in vivo. Animal studies suggest that WF10 enhances immunity against tumors. One possible explanation for such an effect is that WF10 stimulates natural killer cell cytotoxicity against malignant cells. Here, we show that WF10 regulates human NK cell cytotoxicity in a time-dependent manner, following an S-shaped kinetic with an initial stimulation of activity followed by a decrease in activity relative to the untreated controls. WF10 does not activate NK cells on its own but co-stimulates NK cell activation mediated by different activating receptors. This is mediated by enhancing NK cell adhesion to target cells through promoting the activation of the integrin LFA-1. These data demonstrate a direct effect of WF10 on the cytotoxicity of human NK cells.